Comprehensive analysis of the lysine acetylome in Aeromonas hydrophila reveals cross-talk between lysine acetylation and succinylation in LuxS. Issue 1 (1st January 2019) - Sun, Lina; Yao, Zujie; Guo, Zhuang; Zhang, Lishan; Wang, Yuqian; Mao, Ranran; Lin, Yuexu; Fu, Yuying; Lin, Xiangmin
ABSTRACT: Lysine acetylation and succinylation are both prevalent protein post-translational modifications (PTMs) in bacteria species, whereas the effect of the cross-talk between both PTMs on bacterial biological function remains largely unknown. Our previously study found lysine succinylated sites on proteins play important role on metabolic pathways in fish pathogenic Aeromonas hydrophila . A total of 3189 lysine-acetylation sites were further identified on 1013 proteins of this pathogen using LC-MS/MS in this study. Functional examination of these PTMs peptides showed associations with basal biological processes, especially metabolic pathways. Additionally, when comparing the obtained lysine acetylome to a previously obtained lysine succinylome, 1198 sites in a total of 547 proteins were found to be in common and associated with various metabolic pathways. As the autoinducer-2 (AI-2) synthase involved in quorum sensing of bacteria, the site-directed mutagenesis of LuxS at the K165 site was performed and revealed that the cross-talk between lysine acetylation and succinylation exerts an inverse influence on bacterial quorum sensing and on LuxS enzymatic activity. In summary, this study provides an in-depth A. hydrophila lysine acetylome profile and for the first time reveals the role of cross-talk between lysine acetylation and succinylation, and its potential impact on bacterial physiological functions.